Cultivating Conditions for Access: A Case for "Case-Making" in Graduate Student Preparation for Interdisciplinary Research. (April 2017) - Hannah, Mark A.; Arreguin, Alex
Gaining access to interdisciplinary research sites poses unique research challenges to technical and professional communication scholars and practitioners. Drawing on applied experiences in externally funded interdisciplinary research projects and scholarship about interdisciplinary research, this article describes a training protocol for preparing graduate students to understand the dynamic nature of access in interdisciplinary work as well as to develop a capacity for making a case about the value of their expertise in interdisciplinary research contexts. The authors situate the training protocol in the context of three distinct phases of case-making (individual, relational, and speculative) and note how the conditions for negotiating access vary within and across these phases. The authors conclude by describing implications to graduate students and faculty for theorizing access in this way and developing training to support graduate students' negotiation of access in interdisciplinary work.